Perbedaan Perkembangan Bahasa antara Anak yang Bersekolah di TK Sentra dan TK reguler - Tantiva, Ica; Yusuf Muslihin, Heri (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
The purpose of this study was to identify differences in language development between children who go to center-based kindergartens and children who go to regular kindergartens. The method used uses a quantitative approach and statistical analysis (independent sample t-test) to test the hypothesis objectively. The subjects of the study consisted of children aged 4-6 years who attended both types of kindergartens. Language development data were collected through observation and language development tests that measured aspects of speaking, listening, vocabulary, and communication skills. The results showed that children in kindergarten centers had significantly better language development compared to children in regular kindergartens. This is due to the center-based learning model which provides more intensive language stimulation through structured play activities and more interaction